Marketing Strategies for the University Libraries in Kerala - P.K. Suresh Kumar (DESIDOC Journal of Library & Information Technology, 2013)
Libraries have been putting considerable efforts in the design of information products and services and distributing the same effectively and efficiently. In view of the social, economic, and technological changes, library and information centers have begun to realise that marketing of information products and services is an integral part of administration. This paper attempts to work out marketing strategies for the university libraries in Kerala by analysing the marketing orientation through a user survey. The data for the study was collected from a sample of 842 users of the university libraries in Kerala such as Kerala University Library (KUL), Mahatma Gandhi University Library (MGUL), Cochin University of Science and Technology Library (CUSATL), and CH Mohammed Koya Library of University of Calicut (CHMKL). The study found that most of the respondents are willing to pay for information services since they rely more on the quality of information services than the existing fee services. The preferred pricing policy is to provide necessary subsidy to the extent of 50 % based on the payment capacity of various user segments. The survey found that only a few users are aware of existing service offered by the university libraries and there is need for effective promotional strategies. The study suggested various strategies for repositioning the university libraries in Kerala for marketing.